Strategi Pengembangan UMKM oleh Dinas Koperasi Usaha Kecil Menengah dan Perdagangan di Desa Tambaksari Kabupaten Ciamis - Yuni Wandini; Kiki Endah; Aditiyawarman Aditiyawarman (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2025)
This research is motivated by the lack of UMKM Development Strategy by the Office of Small and Medium Enterprises Cooperatives and Trade in Tambaksari Village, Ciamis Regency. The purpose of this study was to determine how the umkm development strategy by the cooperative office of small and medium enterprises and trade in Tambaksari village, Ciamis Regency. The research method used is qualitative research with descriptive analysis. The results showed that the umkm development strategy by the Office of Small and Medium Enterprises Cooperatives and Trade was not optimal, because there were obstacles, namely the lack of purchasing power of the community, the relatively small income of traders, and there was nothing from the Office of Small and Medium Enterprises Cooperatives and Trade related to business capital for business actors. This research can make umkm develop more widely and sustainably and can provide benefits and understanding of umkm development strategies by the Office of Cooperatives, Small and Medium Enterprises and Trade.